Antioxidant and renoprotective effects of paricalcitol on experimental contrast-induced nephropathy model - ÖZEN ALAHDAB, YEŞİM (BRITISH INST RADIOLOGY, 2012)
Objectives: The aim of the study was to assess the effect of paricalcitol on the experimental contrast-induced nephropathy (CIN) model. We hypothesised that paricalcitol may prevent CIN. Methods: 32 Wistar albino rats were divided into four groups (n=8 each): control group, paricalcitol group, CIN group and paricalcitol plus CIN group. Paricalcitol (0.4 mu g kg(-1) day(-1)) was given intraperitoneally for 5 consecutive days prior to induction of CIN. CIN was induced at day 4 by intravenous injection of indometacin (10 mg kg(-1)), N omega-nitro-L-arginine methyl ester (L-NAME, 10 mg kg(-1)) and meglumine amidotrizoate (6 ml kg(-1)). Renal function parameters, oxidative stress biomarkers, histopathological findings and vascular endothelial growth factor (VEGF) immunoexpression were evaluated. Results: The paricalcitol plus CIN group had lower mean serum creatinine levels (p=0.034) as well as higher creatinine clearance (p=0.042) than the CIN group. Serum malondialdehyde and kidney thiobarbituric acid-reacting substances levels were significantly lower in the paricalcitol plus CIN group than in the CIN group (p=0.024 and p=0.042, respectively). The mean scores of tubular necrosis (p=0.024), proteinaceous casts (p=0.038), medullary congestion (p=0.035) and VEGF immunoexpression (p=0.018) in the paricalcitol plus CIN group were also significantly lower. Conclusion: This study demonstrates the protective effect of paricalcitol in the prevention of CIN in an experimental model.
Keywords: ACUTE-RENAL-FAILURE; ENDOTHELIAL GROWTH-FACTOR; COMBINATION THERAPY; OXIDANT STRESS; KIDNEY; INJURY; PATHOGENESIS; PREVENTION; ENALAPRIL; HYPOXIA